Preparation method of nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors

Through the steps of solvent thermal reaction and high-temperature calcination, Ni-MOFs-derived nickel oxide/carbon tube @ hollow carbon composite materials with hollow structure and uniform nitrogen doping were prepared, which solved the problem of preparing hollow MOFs and uniform nitrogen doping in the prior art, and achieved high-performance electrode materials.

CN115512981BActive Publication Date: 2025-04-18DALIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211360126.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2025-04-18
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

The prior art is difficult to prepare hollow MOFs by a one-step method, and uniformly incorporate nitrogen elements into the MOFs-derived metal compound/porous carbon composite, resulting in insufficient conductivity and structural stability.

Method used

Nitrogen-doped Ni-MOFs with hollow structures were prepared by solvothermal reaction using sodium dodecylbenzenesulfonate as an induction reagent, and N-carbon nanotubes were calcined at high temperature to form N-carbon nanotubes. Then, nitrogen-doped MOF-derived metal oxide/carbon tubes @ hollow carbon composite material was prepared by a gentle H2O2 oxidation process.

Benefits of technology

It realizes the simple and efficient preparation of nitrogen-doped MOF-derived nickel oxide/carbon tube @ hollow carbon composite material, which improves the conductivity and electrochemical properties of the material, and is suitable for supercapacitor electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115512981B_ABST
    Figure CN115512981B_ABST
Patent Text Reader

Abstract

A method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material that can be used for supercapacitors, under the premise of adding sodium dodecylbenzene sulfonate, a nickel source is mixed with pyromellitic acid and 3,5-pyrazole dicarboxylic acid for solvent thermal reaction, and a nitrogen-doped Ni-MOFs with a hollow structure is prepared, and then the product is obtained after calcining it in a nitrogen atmosphere and then oxidizing it through a low-concentration H2O2 oxidation process. The present invention does not require a subsequent process to remove a template agent, nor does it require a post-treatment method to obtain a hollow structure, and the method is simple and cost-saving; more active sites can be provided for redox reactions, and sites can also be provided for the growth of carbon nanotubes; hydrogen peroxide can oxidize metal particles under mild conditions to prepare metal oxides, avoid the destruction of the carbon skeleton by conventional high-temperature air oxidation methods, and maintain the structure of carbon materials; space can be effectively utilized to promote the transmission of electrons / ions, and it has higher performance as a capacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and relates to a method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material that can be used for supercapacitors. Background Art

[0002] In recent years, due to the excessive exploitation of fossil fuels and the increasing emission of three wastes during use, environmental pollution problems have become increasingly severe, and efficient, safe and reliable energy storage devices have attracted widespread attention. Supercapacitors (SCs) have attracted widespread attention due to their rapid renewability, ultra-high power density and good long-term cycle stability. Among them, electrode materials, as a key component of SCs, play an important role in improving their electrochemical performance. Therefore, in order to meet the growing demand for energy density, people are striving to seek advanced electrode materials for SCs. MOFs have high porosity and high specific surface area, can provide abundant pores and channels, expose more reaction sites, and are excellent electrode materials. Among them, MOFs with hollow structures can further increase the contact area between electrolyte and electrode materials, and effectively improve electrochemical performance. However, the current preparation of hollow MOFs mostly adopts post-processing methods, which are difficult to form by one-step method, increasing time and environmental costs. (Peilei He, et al., Angew. Chem. Int. Ed. 2017, 56, 3897-3900). In addition, pure MOFs have poor conductivity, and many researchers use MOFs as sacrificial templates to prepare their derived metal compounds / porous carbon composites to improve their electrochemical performance. For example, Yang Li et al. directly converted the Co array into a composite ZIF-67 / Co-based MOF array by chemical vapor deposition (MOF-CVD), and then obtained CoO by calcination. x / Carbon composite array (CoCA). At 1A / g, the specific capacitance can reach 1660.4F / g (ACS Appl. Mater. Interfaces 2021, 13, 41649-41656).

[0003] The introduction of heteroatoms into MOFs-derived metal compounds / porous carbon composites can further improve their conductivity. For example, the common practice of introducing nitrogen atoms is to mechanically mix the prepared porous carbon material or its precursor with nitrogen-containing raw materials such as urea and melamine, and then perform high-temperature treatment to obtain nitrogen-doped porous carbon. For example, the patent with application number 201710009138.1 discloses a method for nitrogen-doped porous carbon, which is to use melamine as a nitrogen source and a carbon-containing precursor for mechanical mixing and high-temperature treatment for preparation. However, mechanical mixing cannot achieve uniform distribution of nitrogen elements, and the introduction of an external nitrogen source is also likely to cause structural collapse of carbon materials, which is not conducive to the maintenance of morphology. For MOFs, nitrogen-containing ligands are usually basic ligands. In the preparation of MOFs with carboxylic acid ligands, it is difficult to introduce basic ligands into the skeleton of MOFs, which makes in-situ nitrogen doping also have great restrictions on the types of MOFs. Therefore, it is difficult to find a relatively simple method to prepare metal compounds / nitrogen-doped hollow carbon through MOFs. Summary of the invention

[0004] The present invention first uses divalent nickel ions as metal nodes, pyromellitic acid as ligands, 3,5-pyrazoledicarboxylic acid as nitrogen-doped ligands, and sodium dodecylbenzenesulfonate as an inducing agent to prepare nitrogen-doped Ni-MOFs with a hollow structure. Subsequently, the metal ions in the MOFs are converted into metal particles by high-temperature calcination. These metal particles further catalyze the residual organic units to form N-carbon nanotubes (N-CNTs) in the presence of nitrogen, which are attached to the hollow carbon surface to form a metal / carbon tube @ hollow carbon composite material. The corresponding metal oxide / carbon tube @ hollow carbon composite material is then prepared by a mild H2O2 oxidation process.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A preparation method of nitrogen-doped MOF-derived nickel oxide / carbon tube @ hollow carbon composite material that can be used for supercapacitors, under the premise of adding sodium dodecylbenzene sulfonate, a nickel source is mixed with pyromellitic acid and 3,5-pyrazoledicarboxylic acid for solvent thermal reaction to prepare nitrogen-doped Ni-MOFs with a hollow structure, which is then calcined at a certain temperature in a nitrogen atmosphere and then oxidized by a simple and mild low-concentration H2O2 oxidation process to obtain a nitrogen-doped MOF-derived metal oxide / carbon tube @ hollow carbon composite material. The steps are as follows:

[0007] (a) Preparation of N-Ni-MOF with hollow structure

[0008] First, pyromellitic acid, sodium dodecylbenzenesulfonate and 3,5-pyrazoledicarboxylic acid (nitrogen doping ligand, achieving in-situ nitrogen doping) were added to N,N-dimethylformamide (DMF), and stirred at room temperature for 30 minutes to obtain solution A. For every 20 mL of N,N-dimethylformamide, 0.5 g of pyromellitic acid, 0.5-1.5 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added.

[0009] Afterwards, a nickel source is added to the DMF solution to obtain solution B, and then solution A is added to solution B, and stirred at room temperature for 30 minutes to obtain a mixed solution. 0.25-1 g of the nickel source is added to each 20 mL of the DMF solution; the nickel source is Ni(NO3)2·6H2O, NiCl2·6H2O, or Ni(SO4)2·6H2O.

[0010] Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 150-170°C for 10-16 hours. After the reaction, it was washed with ethanol and dried in a 60°C oven for 12 hours. The added sodium dodecylbenzene sulfonate can enable MOFs to self-assemble into a hollow structure during the growth process, thus preparing N-Ni-MOF with a hollow structure by a one-step method.

[0011] (b) Preparation of nitrogen-doped MOF-derived metal oxide / carbon tube@hollow carbon composites NiO / N-CNT@HCs

[0012] The N-Ni-MOF prepared in step (a) is calcined at 400-800°C for 1 hour at a rate of 5°C / min in a tubular furnace under a nitrogen atmosphere. During the calcination process, the metal ions in the MOFs are converted into metal particles, which further catalyze the residual organic units to form N-carbon nanotubes (N-CNTs) in the presence of nitrogen, which are attached to the hollow carbon surface to form a metal / carbon tube @ hollow carbon composite material. The synthesized sample is then treated with a hydrogen peroxide solution for 12 hours. The mild oxidation process maintains the hollow carbon structure and avoids the destruction of the carbon skeleton by conventional high-temperature air oxidation methods, and finally obtains a nitrogen-doped MOF-derived metal oxide / carbon tube @ hollow carbon composite material NiO / N-CNT@HCs. The hydrogen peroxide concentration is 3-7wt.%.

[0013] The beneficial effects of the present invention are:

[0014] 1) In the preparation process of the present invention, the added sodium dodecylbenzene sulfonate can make MOFs self-assemble into a hollow structure during the growth process, without the need to remove the template in the subsequent process, and without the need to obtain the hollow structure through post-treatment. The method is simple and saves costs.

[0015] 2) In the preparation process of the present invention, the added 3,5-pyrazoledicarboxylic acid is a nitrogen-doped ligand, which is introduced into MOFs to achieve uniform nitrogen doping. 3,5-pyrazoledicarboxylic acid can be doped with nitrogen, and its carboxyl ligand can be well integrated into the main ligand to maintain the main structure of MOFs, which can provide more active sites for redox reactions and sites for the growth of carbon nanotubes.

[0016] 3) The nickel element obtained at high temperature catalyzes the formation of carbon nanotubes, forming a unique structure of carbon nanotubes grown on the surface of hollow carbon.

[0017] 4) Hydrogen peroxide can oxidize metal particles under mild conditions to prepare metal oxides, avoiding the destruction of the carbon skeleton by conventional high-temperature air oxidation and maintaining the structure of the carbon material.

[0018] 5) Metal oxide / carbon tube@hollow carbon composite materials can effectively utilize space, promote the transmission of electrons / ions, and have higher performance as capacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM photograph of the N-Ni-MOF sample of Example 1.

[0020] Figure 2 This is the SEM photo of the NiO / N-CNT@HCs sample of Example 1. DETAILED DESCRIPTION

[0021] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0022] Example 1

[0023] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF with a hollow structure.

[0024] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with a 5wt.% hydrogen peroxide solution for 12h to obtain nitrogen-doped MOF-derived metal oxide / carbon tube@hollow carbon composite material NiO / N-CNT@HCs.

[0025] The nitrogen content was 7.6 wt. % as determined by elemental analysis.

[0026] Using it as a capacitor electrode material, the three-electrode test shows that the specific capacitance can reach 1948F / g at 0.5A / g. Under 1A / g, 2A / g, 5A / g, and 10A / g tests, the specific capacitance is 1876, 1795, 1713, and 1642F / g, and the rate retention is above 85%.

[0027] Example 2

[0028] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzene sulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of NiCl2·6H2O was added to 20 mL of DMF solution to obtain solution B, and then solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0029] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0030] The nitrogen content was 7.2 wt. % as determined by elemental analysis.

[0031] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1638F / g under 0.5A / g conditions.

[0032] Example 3

[0033] First, 0.5 g of pyromellitic acid, 0.5 g of sodium dodecylbenzene sulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and then solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 150 ° C for 16 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0034] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0035] The nitrogen content was 7.3 wt. % as determined by elemental analysis.

[0036] Using it as a capacitor electrode material, the three-electrode test shows that the specific capacitance can reach 1687F / g at 0.5A / g. Under the test conditions of 1A / g, 2A / g, 5A / g, and 10A / g, the specific capacitance is 1535, 1452, 1396, and 1219F / g, and the rate retention is above 70%.

[0037] Example 4

[0038] First, 0.5 g of pyromellitic acid, 1.5 g of sodium dodecylbenzene sulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and placed in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0039] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0040] The elemental analysis showed that the nitrogen content was 7.0wt.%.

[0041] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1376F / g under 0.5A / g conditions.

[0042] Example 5

[0043] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0044] The prepared N-Ni-MOF was calcined at 400°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with a 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs. The nitrogen content was 7.2wt.% as determined by elemental analysis.

[0045] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1541F / g under 0.5A / g conditions.

[0046] Example 6

[0047] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0048] The prepared N-Ni-MOF was calcined at 800°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0049] The nitrogen content was 6.9 wt. % as determined by elemental analysis.

[0050] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1286F / g under 0.5A / g conditions.

[0051] Example 7

[0052] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 1 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0053] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0054] According to elemental analysis, the nitrogen content is 7.4wt.%.

[0055] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1714F / g under 0.5A / g conditions.

[0056] Example 8

[0057] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzene sulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.25 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 170 ° C for 10 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0058] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 5wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0059] The nitrogen content was found to be 6.6 wt. % by elemental analysis.

[0060] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1032F / g under 0.5A / g conditions.

[0061] Example 9

[0062] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0063] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 3wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0064] The nitrogen content was 7.2 wt. % as determined by elemental analysis.

[0065] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1589F / g under 0.5A / g conditions.

[0066] Example 10

[0067] First, 0.5 g of pyromellitic acid, 1 g of sodium dodecylbenzenesulfonate and 0.4 g of 3,5-pyrazoledicarboxylic acid were added to 20 mL of N,N-dimethylformamide (DMF) and stirred at room temperature for 30 min to obtain solution A. Then, 0.5 g of Ni(NO3)2·6H2O was added to 20 mL of DMF solution to obtain solution B, and solution A was added to solution B and stirred at room temperature for 30 min to obtain a mixed solution. Finally, the mixed solution was placed in a polytetrafluoroethylene-lined autoclave and reacted at 160 ° C for 12 h. After the reaction was completed, it was washed with ethanol and dried in a 60 ° C oven for 12 h to obtain N-Ni-MOF.

[0068] The prepared N-Ni-MOF was calcined at 600°C for 1 hour at a rate of 5°C / min in a tube furnace under nitrogen atmosphere. The synthesized sample was then treated with 7wt.% hydrogen peroxide solution for 12h to obtain NiO / N-CNT@HCs.

[0069] The nitrogen content was 6.7 wt. % as determined by elemental analysis.

[0070] Using it as a capacitor electrode material, three-electrode testing shows that the specific capacitance can reach 1093F / g under 0.5A / g conditions.

[0071] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors, characterized in that: Under the condition of adding sodium dodecylbenzene sulfonate, the nickel source was mixed with isophthalic acid and 3,5-pyrazoledicarboxylic acid for solvothermal reaction to prepare nitrogen-doped Ni-MOFs with a hollow structure. Subsequently, it was calcined in a nitrogen atmosphere and then oxidized by a low-concentration H2O2 oxidation process to obtain nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite materials.

2. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 1, characterized in that: Here are the steps: The first step is to prepare N-Ni-MOF with a hollow structure 1.1) Add pyromellitic acid, sodium dodecylbenzenesulfonate and 3,5-pyrazoledicarboxylic acid into N,N-dimethylformamide (DMF) and stir at room temperature for 30 min to obtain solution A; 1.2) adding a nickel source to a DMF solution to obtain a solution B, and then adding a solution A to the solution B, stirring at room temperature for 30 min to obtain a mixed solution; wherein the volume ratio of the solution A to the solution B is 1:1; 1.3) placing the mixed solution into a polytetrafluoroethylene-lined autoclave, reacting at 150-170° C. for 10-16 hours, and after the reaction, washing and drying to obtain a N-Ni-MOF having a hollow structure; The second step is to prepare nitrogen-doped MOF-derived metal oxide / carbon tube@hollow carbon composite NiO / N-CNT@HCs The N-Ni-MOF prepared in the first step is heated from room temperature to 400-800°C in a tubular furnace under a nitrogen atmosphere and calcined for 1 hour. During the calcination process, the formed N-carbon nanotubes (N-CNTs) adhere to the surface of the hollow carbon to form a metal / carbon tube@hollow carbon composite material; it is then treated with a hydrogen peroxide solution for 12 hours to obtain a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material.

3. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 2, characterized in that: In the step 1.1), 0.5 g of pyromellitic acid, 0.5-1.5 g of sodium dodecylbenzenesulfonate, and 0.4 g of 3,5-pyrazoledicarboxylic acid are added to every 20 mL of N,N-dimethylformamide.

4. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 2, characterized in that: In the step 1.2), 0.25-1 g of nickel source is added to every 20 mL of DMF solution.

5. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 2, characterized in that: In the step 1.2), the nickel source is Ni(NO3)2·6H2O, NiCl2·6H2O, or Ni(SO4)2·6H2O.

6. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 2, characterized in that: In the second step, the heating rate from room temperature to calcination temperature is 5°C / min.

7. The method for preparing a nitrogen-doped MOF-derived nickel oxide / carbon tube@hollow carbon composite material for supercapacitors according to claim 2, characterized in that: In the second step, the concentration of hydrogen peroxide is 3-7wt.%.

Citation Information

Patent Citations

  • A nitrogen-doped porous carbon, its preparation method, and its application as a supercapacitor electrode material.

    CN106629724B

  • Bismuth vanadate composite photocatalytic material and preparation method thereof

    CN112871194A

  • Preparation method and application of unsaturated coordination manganese-based metal organic framework composite material

    CN113444257A